Dari Perilaku Menuju Pilihan: Memahami Pembentukan Preferensi Wisatawan dan Pola Pengeluaran di Banyuwangi Sebagai Destinasi Alternatif Berkembang - Margaretta Andini Nugroho; Edy Wahyudi; Galih Wicaksono; Agus Suharsono; Akhmad Munif Mubarok; Sri Yuniati (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the influence of tourist behaviour on visit decisions with tourist preference and expenditure behaviour as mediating variables in Banyuwangi Regency as an alternative destination. A quantitative approach with positivism paradigm was employed. Data were collected through questionnaires from 834 tourists visiting various tourist attractions in Banyuwangi. Data analysis utilized Partial Least Squares (SEM-PLS) with SmartPLS 4. The results showed that all hypotheses were accepted. Tourist behaviour, tourist preference, and expenditure behaviour partially and simultaneously have positive and significant effects on visit decisions, with expenditure behaviour as the strongest predictor (β=0.265; t=6.730). Tourist preference mediates the relationship between tourist behaviour and visit decisions (indirect effect=0.043; t=3.429). Expenditure behaviour also mediates this relationship (indirect effect=0.082; t=5.222). Furthermore, tourist preference and expenditure behaviour serially mediate the relationship between tourist behaviour and visit decisions (indirect effect=0.023; t=4.355). These findings confirm that tourists' decisions to visit alternative destinations are not only determined by internal factors but also through preference formation and economic behaviour. This research contributes to the development of consumer behaviour theory in tourism and provides practical guidance for destination managers in formulating effective marketing strategies.